2018
DOI: 10.2981/wlb.00351
|View full text |Cite
|
Sign up to set email alerts
|

Dietary preference of Malayan sun bear Helarctos malayanus in Namdapha Tiger Reserve, Arunachal Pradesh, India

Abstract: We characterized the dietary pattern of Malayan sun bear Helarctos malayanus from three seasons in Namdapha tiger reserve, Arunachal Pradesh, India. Eighty ive scat samples were collected between August 2008 and November 2010. Scats were analysed both qualitatively and quantitatively to determine the food composition of sun bear in the region. he contents were manually separated and examined. Cumulative frequency was used to determine the contribution of food items in the diet of sun bear. Malayan sun bear was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…All canids are terrestrial aside from Urocyon cinereoargenteus (gray fox—one of the smallest canid species) (Nowak & Walker, 1999; Trapp & Hallberg, 1975), which has been known to climb trees to escape from predators (Haltenorth & Roth, 1968; Trapp & Hallberg, 1975). Unlike the almost exclusively terrestrial canids, several ursid species are regularly arboreal, vertically climbing to reach food or shelter (Larivière, 2001; Nakajima et al, 2018; Peyton, 1980; Sethy & Chauhan, 2018; Taylor, 1989), and Ursus maritimus (polar bear), is a strong swimmer that lives on pack ice in artic regions (Stroganov, 1969). Artiodactyls in general have evolved long, slender legs, but some large bovids have relatively short legs and large feet that are thought to aid in stability during stationary defense against predators (Klein, 1992; Scott, 1985), and some species of cervid (e.g.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…All canids are terrestrial aside from Urocyon cinereoargenteus (gray fox—one of the smallest canid species) (Nowak & Walker, 1999; Trapp & Hallberg, 1975), which has been known to climb trees to escape from predators (Haltenorth & Roth, 1968; Trapp & Hallberg, 1975). Unlike the almost exclusively terrestrial canids, several ursid species are regularly arboreal, vertically climbing to reach food or shelter (Larivière, 2001; Nakajima et al, 2018; Peyton, 1980; Sethy & Chauhan, 2018; Taylor, 1989), and Ursus maritimus (polar bear), is a strong swimmer that lives on pack ice in artic regions (Stroganov, 1969). Artiodactyls in general have evolved long, slender legs, but some large bovids have relatively short legs and large feet that are thought to aid in stability during stationary defense against predators (Klein, 1992; Scott, 1985), and some species of cervid (e.g.…”
Section: Methodsmentioning
confidence: 99%
“…Urocyon cinereoargenteus (gray fox-one of the smallest canid species) (Nowak & Walker, 1999;Trapp & Hallberg, 1975), which has been known to climb trees to escape from predators (Haltenorth & Roth, 1968;Trapp & Hallberg, 1975 climbing to reach food or shelter (Larivière, 2001;Nakajima et al, 2018;Peyton, 1980;Sethy & Chauhan, 2018;Taylor, 1989),…”
Section: Taxon Frequency Of Arboreal Behaviormentioning
confidence: 99%
“…Signs of insect feeding, though, are hard to detect and thus may underestimate actual use of this food. One study in Northeast India, based on scats, found that insects composed nearly half the annual diet (Sethy and Chauhan 2018), and another found that sun bears commonly used a degraded bamboo forest due to an abundance of termites (Gouda et al 2020). This dimension of the sun bear diet is often neglected when conservationists debate the value of logged areas.…”
Section: Conservation Value Of Logged Forestsmentioning
confidence: 99%
“…Several surveys and documentation have been carried out in Arunachal Pradesh on large and small mammals (Athreya et al, 1997;Chowdhury, 1997;Datta, 1998;Datta et al, 2008a;Mishra et al, 2006;Gopi et al, 2010;Gopi et al, 2012;Selvan, 2013;Dasgupta et al, 2014;Selvan et al, 2014b;Dasgupta et al, 2015;Adhikarimayum and Gopi, 2018), Malayan sun bear (Sethy and Chauhan, 2012) and red panda (Kakati, 1996). Most wildlife surveys in Arunachal have been restricted to low and mid-elevation forests and have focused on rare species Athreya and Johnsingh, 1995;Selvan et al, 2013;Roy et al, 2015).…”
Section: Introductionmentioning
confidence: 99%